Improved combustion kinetic model and HCCI engine simulations of di-isopropyl ketone ignition. (15th January 2016) - Barari, Ghazal; Sarathy, S. Mani; Vasu, Subith S.
Abstract: Di-isopropyl ketone (DIPK) is considered a promising biofuel candidate produced using endophytic fungal conversion. In the current study, homogeneous charge compression ignition (HCCI) simulations of DIPK engine experiments were conducted with single-zone and multi-zone engine models. Both adiabatic and non-adiabatic single-zone HCCI models were explored. The non-adiabatic model employed the Woschni correlation to account for heat transfer observed in the experiments. The HCCI simulations utilized a literature DIPK kinetic model with slight modifications to better reproduce experimental data. The modifications were done by including additional intermediate species and radical reactions, which were not considered in the original reaction mechanism. In addition, zero dimensional simulations were conducted to validate the updated model against limited shock tube and pyrolysis experimental data available in the literature. The single-zone model of HCCI engine with the updated kinetic model provided good agreement for pressure during compression until ignition, however, it over predicted the peak pressure, as expected. The improved kinetic mechanism was able to predict the pressure, heat release rate, and temperature in a 5-zone model of HCCI engine with good agreement to the experiments. Brute force sensitivity analyses revealed that the most sensitive reaction in which DIPK participates is the H-abstraction reaction from the fuel by HO2 . Discussions are provided on the validity of the DIPK model in comparison with the parametric engine data over a range of temperature, pressure, equivalence ratio, and engine speed.